Patterns of interaction in young EFL learners’ pair work: the relationship between pair dynamics and vocabulary acquisition - Ahmadian, Moussa; Tajabadi, Azar (Penerbit Universiti Kebangsaan Malaysia, 2017)
Adopting a social learning perspective towards the interface between the use of pair work and language learning, the present study investigated the dyadic interaction in an EFL course for young learners at preelementary school level. A number of 18 EFL learners were put into 9 pairs and received instructions on 24 target vocabulary items during 6 sessions. In each session, the participants completed a recognitions task and a production task. Their dialogues were recorded, transcribed, and coded as exhibiting one of the four patterns: collaborative, expert/novice, dominant/dominant, and dominant/passive based on Storch’s (2002) patterns of interaction coding scheme. The comparison between the patterns and the participants’ performance on a vocabulary test revealed that collaborative and expert/novice were associated with better learning outcomes. The findings are discussed along with Vygotsky’s sociocultural theory and pedagogical implications for trainers and instructors.